Ukraine in histories and stories essays by Ukrainian intellectuals - Jermolenko, Volodymyr Anatolijovyč 1980-; Kurkov, Andrij Jurijovyč 1961-; Hrycak, Jaroslav Josypovyč 1960-; Plokhy, Serhii 1957-; Andruchovyč, Jurij Ihorovyč 1960-; Šelest, Hanna; Šyjan, Halyna Romanivna 1980- (Internews Ukraine, 2019)
The book is a collection of texts by contemporary Ukrainian intellectuals: writers, historians, philosophers, political analysts, opinion leaders. The texts have been written for an international audience. The collection combines reflections on Ukraine's history (or histories, in plural), and analysis of the present, conceptual ideas and life stories. The book presents a multi-faceted image of Ukrainian memory and reality: from the Holodomor to Maidan, from Russian aggression to cultural diversity, from the depth of the past to the complexity of the present.--
Keywords: History; Ukraine / History; Ukraine / Social life and customs; Histoire; Ukraine / Histoire; history (discipline); Manners and customs; Ukraine / https://id.oclc.org/worldcat/entity/E39PBJkMMfGYRhk8WcWRp3xJjC